Heterozygous variants in ACTL6A, encoding a component of the BAF complex, are associated with intellectual disability. Issue 10 (10th July 2017) - Marom, Ronit; Jain, Mahim; Burrage, Lindsay C.; Song, I‐Wen; Graham, Brett H.; Brown, Chester W.; Stevens, Servi J.C.; Stegmann, Alexander P.A.; Gunter, Andrew T.; Kaplan, Julie D.; Gavrilova, Ralitza H.; Shinawi, Marwan; et al.
Abstract : Pathogenic variants in genes that closely interact with the BRG1‐associated factor (BAF) complex have been associated with intellectual disability. We identified heterozygous variants ACTL6A, a scaffold component of the BAF complex, in three subjects with developmental delay and varying degree of learning disabilities. All variants are predicted to result in loss‐of‐function. We suggest that sequencing of ACTL6A should be considered in the diagnostic work‐up of developmental delay and learning disabilities. Abstract: Pathogenic variants in genes encoding components of the BRG1‐associated factor (BAF) chromatin remodeling complex have been associated with intellectual disability syndromes. We identified heterozygous, novel variants in ACTL6A, a gene encoding a component of the BAF complex, in three subjects with varying degrees of intellectual disability. Two subjects have missense variants affecting highly conserved amino acid residues within the actin‐like domain. Missense mutations in the homologous region in yeast actin were previously reported to be dominant lethal and were associated with impaired binding of the human ACTL6A to β‐actin and BRG1. A third subject has a splicing variant that creates an in‐frame deletion. Our findings suggest that the variants identified in our subjects may have a deleterious effect on the function of the protein by disturbing the integrity of the BAF complex. Thus, ACTL6A gene mutation analysis should be considered in patients with intellectual disability, learning disabilities, or developmental language disorder.